2021
DOI: 10.1007/s11845-021-02751-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the mother’s choice of infant feeding method in Poland: a cross-sectional preliminary study in Poland

Abstract: Background The World Health Organization identifies exclusive breastfeeding as the gold standard for child nutrition. Breastfeeding provides many benefits to both the baby and the mother. First days after birth are crucial for breastfeeding and determining its further path. Unfortunately, very often it is also the time of facing the first breastfeeding problems. The aim of this study was to analyse selected factors influencing a mother’s decision to breastfeed. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
3
1
Order By: Relevance
“…The main reasons for the initiation of formula feeding in this study were insufficient breast milk (42.3%), being busy with work (34.6%), and sluggish baby growth (23.1%). Similar to studies conducted in Dire-Dawa that reported breast milk insufficiency (85%) and busy with work (10%) (Dagne et al, 2019), Hangzhou and Shenzhen, China, reported perceived insufficient breast milk (86.2%), followed by a return to work (24.6%) (Tang et al, 2014), while in Poland, 62% of participants reported perceived insufficient breast milk (Rozensztrauch et al, 2021).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The main reasons for the initiation of formula feeding in this study were insufficient breast milk (42.3%), being busy with work (34.6%), and sluggish baby growth (23.1%). Similar to studies conducted in Dire-Dawa that reported breast milk insufficiency (85%) and busy with work (10%) (Dagne et al, 2019), Hangzhou and Shenzhen, China, reported perceived insufficient breast milk (86.2%), followed by a return to work (24.6%) (Tang et al, 2014), while in Poland, 62% of participants reported perceived insufficient breast milk (Rozensztrauch et al, 2021).…”
Section: Discussionsupporting
confidence: 77%
“…The prevalence of formula feeding in this study is comparable with a study conducted in Agaro Town, which was found to be 29% (Seid et al, 2019), and Dire‐Dawa, which was 21.4% (Dagne et al, 2019), whereas it was higher compared to the study conducted at Holeta (13.5%) (Kebebe & Assaye, 2017) and Gonder (12.4%) (Asfaw Admasu, 2016). The prevalence of formula feeding in this study was lower compared to the study conducted in Jimma (65%) (Abebe et al, 2019), Adis Abeba 47% (Taye et al, 2021), China 88% (Tang et al, 2015), Staten Island, New York 65% (Pierro et al, 2016), Pakistan 38% (Ijaz et al, 2015), Poland 42% (Rozensztrauch et al, 2021), East Malaysia 73.7% (Yee & Chin, 2007), Egypt 47% (Tawfik et al, 2019), and Nigeria 38.3% (Leshi & Sanusi, 2014). The inconsistency could be attributed to the result of differences in the current study's operational definition of formula feeding, socioeconomic status differences among study participants, and study period.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The literature identi ed that mothers returning to work was a signi cant predictor of intention to continue breastfeeding [21]. Other common breastfeeding problems reported were pain and perceived inadequate breastmilk [27]. A qualitative study identi ed perceived challenges to breastfeeding including judgement from others for breastfeeding in the public or using a bottle, even with expressed breastmilk [28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, encouraging students to actively participate in classroom discussions and making sure they are active listeners and contribute their own ideas through formal discussion can be beneficial for them to understand complex topics more easily. This would help prepare future health professionals to guide families about the benefits and risks of different types of nutrition, as well as provide the necessary skills to recognize and treat complications related to this process [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%